Gloeodontia yunnanensis sp. nov. (Russulales, Basidiomycota) from China, evidenced by morphological characters and phylogenetic analyses - Chen, Lu; Shi, Zheng-Jun; Wu, Chun-Hua; Zhao, Chang-Lin (Phytotaxa, 2020)
A new wood-inhabiting fungal species, Gloeodontia yunnanensis, is proposed based on a combination of morphological features and DNA data. The species is characterized by an annual, resupinate basidiomata with smooth hymenial surface, a monomitic hyphal system with thin-walled, clamped generative hyphae and obclavate cystidia and subglobose to globose, hyaline, thick-walled, asperulate, strongly amyloid, acyanophilous basidiospores measuring 3.3–4.3 × 2.5–3.5 µm. Sequences of ITS and 28S gene regions of the studied samples were generated and phylogenetic analyses were performed with Maximum Likelihood, Maximum Parsimony and Bayesian Inference methods. The analyses based on ITS+28S sequences showed that G. yunnanensis nested in the Gloeodontia clade and formed a monophyletic lineage with strong support (100% BS, 100% BP, 1.00 BPP).